A atualidade da proposta pedagógica Deweyana: um estudo na Escola da Floresta - Possel, Bianca (2020)
The present dissertation starts from the assumption that the pedagogical organization of a school needs to contemplate the current educational policies, but that, however, these do not prevent schools from having innovative initiatives and being able to do creative work and outside the recurring standard. Thus, the main objective of the research is to analyze the currentness of the Dewey’s pedagogical proposal from a case study at the Escola de Ensino Fundamental da Floresta Olho da Coruja (EFOC), located in the countryside of Chapada, RS. The aim of this study is to describe the organization and conduct of pedagogical work in that school in order to understand how educational experiences happen and to point out the feasibility of such innovative experiences in Brazilian schools in view of the current educational policies. The dissertation has as its theoretical fabric Dewey concepts such as education, experience, continuity and interaction, democracy, trust, freedom, autonomy and authority. The problem consists of investigating: What are the contributions of reading the educational proposal of EFOC from Dewey's educational theory to the creative reorganization of learning and school spaces based on current educational policies? In order to seek a satisfactory answer to the proposed problem, the deductive-analytical method is used, since it will start from the Dewey educational proposal to analyze the specific case of EFOC. Research is of a basic nature; as for its objectives, it has an exploratory and descriptive character; the approach to the problem is qualitative; and, as for the procedures, it is bibliographic and a case study. The first chapter presents the theoretical framework, that is, the main concepts that support John Dewey's pedagogical proposal; in the second chapter the description of the organization and the conduct of the pedagogical work carried out by EFOC is carried out. Finally, in the third chapter, the data analysis is developed, that is, a reading of EFOC based on the Dewey’s theory and pointing out the main innovations carried out by the school. The research results pointed to the currentness of the Dewey’s pedagogical proposal and indicate that an innovative school proposal requires theoretical anchoring, definition of a pedagogical proposal, pedagogical and methodological clarity, planning, qualified teachers, confidence of the school community, willingness to learn and recognition of current educational policies as guidelines and not limiting school potential. Innovation occurs when (a) the experimentation of the school as a way of life where, democratically, educational experiences are projected and carried out through interaction with the environment, with peers and with knowledge; (b) the permanent reconstruction of the experience by encouraging children's autonomy, freedom and self-confidence, respecting their development, curiosity and sensitivity; (c) carrying out educational projects, creating materials and exploring nature; (d) the pedagogical freedom experienced by teachers and the exercise of authority without being authoritarian; (e) respect for educational policies, but going beyond it and proposing community learning where the center of the process - where all efforts converge - is learning through the reconstruction of experience.